Strategic outsourcing and corporate performance of quoted insurance firms in Nigeria - Amechi Fabian Anoke; Ndidiamaka Joy Okafor; Anthonia Nkechi Onu (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study is aimed at determining the effect of strategic outsourcing and corporate performance of quoted insurance firms in Nigeria Research methodology: The study adopted a survey research design because it is suitable and ideal for assessing how effective outsourcing strategy affects the corporate performance of insurance firms in Nigeria. With a population of 720 staff from three quoted insurance firms in Nigeria, using Yamane's formula, a sample of 260 respondents was selected. Multiple regression was used to test the hypotheses that were developed at a significance level of 0.05 percent. Results: The study unveiled that outsourcing has evolved into a helpful strategy and weapon for corporate organizations, particularly for Nigerian insurance companies that are constantly looking to improve their corporate performance in the financial sector. Limitations: This study is limited to quoted insurance firms in Nigeria as of December 2021; hence, the result may not be universal to other excluded categories.  It is expected that further studies should cover all the insurance firms in Nigeria with variables like comprehensive and ICT outsourcing strategies on the operational efficiency and profitability of insurance firms in Nigeria. Contributions: To leverage the services of other organizations and professionals outside of their core competencies for operational effectiveness and efficiency, corporate organizations in Nigeria, especially those in the financial sector, should incorporate strategic outsourcing into their corporate culture.